The relationship between public and private higher education in Zambia with a specific focus on the movement of lecturers across public and private universities - Chisembele, John (School of Education, 2024)
Studies conducted on the political economy of higher education in Zambia have inadequately tackled the impacts of neoliberalism on public universities in relation to public lecturers' motivation to teach for both public and private universities and implications for students' learning experiences in public universities. This study investigated the motivations of public university lecturers to teach for both public and private universities. The study also determined the implications of learning for students at the Public University where these lecturers were full-time employees. The main research question driving the study is: What are the implications of lecturers at public universities working simultaneously at private universities? This study is qualitative and phenomenological in nature in that it reported the participants' lived perspectives. The participants in the study comprise four lecturers and four postgraduate students. The responses from the participants were collated according to themes. The findings indicated that the motivations of public university lecturers to teach for both public and private universities were: socio-economic in that lecturers stressed the importance of additional remuneration that public university lecturers received from private universities; benevolence in the form of lecturers offering their service for purposes of creating capacity in new private universities; and management skills gained through positions of leadership that junior public university lecturers were given in private universities which they otherwise would not hold in public universities. The Public University postgraduate students perceived their lecturers' teaching for both public and private universities as retrogressive to the student learning experience in the public university because of: inadequate supervision of postgraduate studies due to teaching overloads by lecturers; time overrun of writing of postgraduate research theses; cost overrun through payment of additional annual tuition fees and inadequate academic mentorship which compromised the quality of their education. The results lead to the conclusion that dual employment practices by some public university lecturers engaged in both public and private universities have distinctly negative implications for the learning experiences of their students at the Public University. This study provides insights for policymakers, policy analysts and academic researchers on higher education in relation to the impacts of neoliberalism and privatisation on the political economy of higher education in Zambia, sub-Saharan Africa, and the Global South.